Comparison of Therapeutic Response and Clinical Outcome between HCV Patients with Normal and Abnormal Alanine Transaminase Levels. - Cheng-Kung Wu; Kuo-Chin Chang; Po-Lin Tseng; Sheng-Nan Lu; Chien-Hung Chen; Jing-Houng Wang; Chuan-Mo Lee; Ming-Tsung Lin; Yi-Hao Yen; Chao-Hung Hung; Tsung-Hui Hu (PLoS ONE)
Background and aims Patients with chronic hepatitic C (HCV) infection and normal serum alanine transaminase (ALT) levels were considered to have mild disease. In Taiwan, these patients were not suggested for interferon (IFN) based therapies. The aim of study is to compare therapeutic outcomes between HCV patients with normal and elevated ALT levels. Methods We conducted a retrospective study on 3241 HCV patients treated by IFN based therapies. Patients with normal ALT levels were classified as group A (n = 186) while those with elevated ALT levels were group B (n = 3055). Results At baseline, incidence of diabetes mellitus, low platelet counts and cirrhosis were significantly higher in group B patients. The sustained virologic response (SVR) rate was comparable between the 2 groups (65.3% vs. 65.3%, P = .993). But significantly higher incidence of HCC development after HCV treatment was observed in group B (7.4% vs. 3.2%, P = .032). No significant differences with respect to the outcome of liver decompensation, spontaneous bacterial peritonitis, and mortality were noted between 2 groups. Multivariate analysis showed younger age, female gender, non-HCV genotype 1, lower viral load, higher platelet counts and non-cirrhosis were favorable factors for achieving SVR, rather than ALT levels. Further analysis revealed older age, cirrhosis, lower platelet levels and non- peg-interferon treatment are risk factors of HCC development. Conclusions HCV patients with normal ALT levels had similar response to antiviral therapy and low rate of HCC development after therapy. Antiviral therapies begun at early course of HCV infection may be beneficial to prevent disease progression.